Recognizing, Assessing, and Responding to Children's Interpersonal Sexual Behavior - Yeh-chen Kuo (National Taipei University of Education, 2020)
The assessments and responses of early childhood workers (ECWs) to children's interpersonal sexual behaviors (ISBs) are especially crucial in the early childhood stage du to their roles. They are not only educators and protectors but also mandated to report suspected cases of child sexual abuse and are expected to reduce the chances that children develop offender's behaviors. In the first part of this article, normative data about children's ISBs to delineate the boundaries of typical and atypical ISB in young children is presented. In the second part, literature about how ECWs responded to children's ISBs and the factors that influenced their responses are reviewed. Assessment and suggestions for ECW regarding how to respond to children's ISBs are discussed in the third part of the article. The three dimensions developed by Gail Ryan - lack of consent, lack of equality, or coercion in the interaction -were proposed to explain to children why their behaviors would be perceived as problematic. In the last part of this article, implications of this overview for ECW's training and future research were proposed. This article benefits ECWs by providing a comprehensive framework for recognizing, assessing, and responding to children's ISBs. Informed by this article, ECWs will be able to protect young children and promote their healthy sexuality development.